2013
DOI: 10.1021/am400110y
|View full text |Cite
|
Sign up to set email alerts
|

Photobias Instability of High Performance Solution Processed Amorphous Zinc Tin Oxide Transistors

Abstract: The effects of the annealing temperature on the structural and chemical properties of soluble-processed zinc-tin-oxide (ZTO) films were examined by transmission electron microscopy, atomic force microscopy, high resolution X-ray reflectivity, and X-ray photoelectron spectroscopy. The density and purity of the resulting ZTO channel layer increased with increasing annealing temperature, whereas the oxygen vacancy defect density decreased. As a result, the device performance of soluble ZTO thin film transistors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 34 publications
(43 reference statements)
1
47
2
Order By: Relevance
“…[25] Nonetheless, the In-based metal oxides are not the ideal semiconductor materials for large-area integrated circuits because of the scarcity of In. [26][27][28] As a result, ZnO is usually adopted as the alternative "In-free" active material for metal-oxide-based electronic devices. [29][30][31] In this regard, the electrospun ZnO NFs have the great potential to satisfy all the stringent requirements for practical applications in large-area, low-cost, and high-performance integrated circuits.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Nonetheless, the In-based metal oxides are not the ideal semiconductor materials for large-area integrated circuits because of the scarcity of In. [26][27][28] As a result, ZnO is usually adopted as the alternative "In-free" active material for metal-oxide-based electronic devices. [29][30][31] In this regard, the electrospun ZnO NFs have the great potential to satisfy all the stringent requirements for practical applications in large-area, low-cost, and high-performance integrated circuits.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known that a combination of additional materials, annealing, or post-deposition processing at high temperature is effective at improving transistor performance. For example, Kwack and W.-S. Choi 2 and Kim et al 3 have reported solution-processed Zinc tin oxide (ZTO) TFTs with carrier mobilities of 4.9 and 6.0 cm 2 /Vs using a high temperature annealing processes at 300 C and 500 C, respectively. Much research is now focused on postdeposition processing as part of an effort to keep the temperature below 150 C. Indium zinc oxide (IZO) TFTs have achieved a mobility of 1.8 cm 2 /Vs by using high-pressure annealing (HPA) following thermal annealing at 220 C. 4 Similarly, UV light irradiation 5 and microwave-assisted annealing 6 have been adopted as useful post-deposition processes.…”
mentioning
confidence: 99%
“…As the annealing temperature increased, the relative area of peak 3 decreased, which may indicate that the hydroxyl groups (M-OH) were converted to oxides [22]. Simultaneously the O 1s peaks shifted toward the lower binding energy, it was reasonable to assume that the hydrolyzed oxide converted into oxide AIZO as the temperature increased [23].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 Moreover, the 300 o C annealed films contained the largest concentration of OH groups as shown in figure 4. This may be due to the more incomplete decompositions of organic ligands and metal salts existed at low annealing temperatures, which would cause the excessive incorporation of Cl and N ions and OH groups [22]. With increasing the annealing temperature, impurities with Cl and N ions were reduced substantially with the enhanced decomposition and evaporation.…”
Section: Resultsmentioning
confidence: 99%